Hemodynamic Instability During Liver Transplantation in Patients With End-stage Liver Disease: A Consensus Document from ILTS, LICAGE, and SATA. Issue 10 (1st October 2021) - Bezinover, Dmitri; Mukhtar, Ahmed; Wagener, Gebhard; Wray, Christopher; Blasi, Annabel; Kronish, Kate; Zerillo, Jeron; Tomescu, Dana; Pustavoitau, Aliaksei; Gitman, Marina; Singh, Anil; Saner, Fuat H.
Abstract : Supplemental Digital Content is available in the text. Abstract : Hemodynamic instability (HDI) during liver transplantation (LT) can be difficult to manage and increases postoperative morbidity and mortality. In addition to surgical causes of HDI, patient- and graft-related factors are also important. Nitric oxide–mediated vasodilatation is a common denominator associated with end-stage liver disease related to HDI. Despite intense investigation, optimal management strategies remain elusive. In this consensus article, experts from the International Liver Transplantation Society, the Liver Intensive Care Group of Europe, and the Society for the Advancement of Transplant Anesthesia performed a rigorous review of the most current literature regarding the epidemiology, causes, and management of HDI during LT. Special attention has been paid to unique LT-associated conditions including the causes and management of vasoplegic syndrome, cardiomyopathies, LT-related arrhythmias, right and left ventricular dysfunction, and the specifics of medical and fluid management in end-stage liver disease as well as problems specifically related to portal circulation. When possible, management recommendations are made. Abstract :